Development and Stability of Bioactive Compounds in Carbonated Black Ice Tea Beverage: Development of carbonated black ice tea beverage - Ahmad Din; Muhammad Nadeem; Saima Parveen; Moazzam Rafique Khan; Masooma Munir; Arshad Mahmood; Muhammad Luqman (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2019)
The aim of present research project was to investigate potential use of black tea extracts to develop carbonated beverage from indigenous raw material. Healthy and nutritious black ice tea beverages were developed with different levels of extracts. Carbonated black ice tea samples were subjected to analyze after one-month interval for total soluble solids, pH, sugars and ascorbic acid content up to period of 90 days. Changes in bioactive compounds in terms of total phenolic contents, theaflavins and DPPH free radical scavenging activity were also investigated. The storage study showed that total soluble solids, titratable acidity and reducing sugars increased whereas decline in pH, ascorbic acid, total phenolic contents, theaflavins, thearubigins and DPPH free radical scavenging activity was observed. Results of sensory evaluation indicated that carbonated black ice tea beverage with 0.2% black tea extract was highly acceptable at 5°C storage conditions. In Pakistan, because of prolonged summer season, there must be an alternate of hot black tea. Iced black tea will be a good option for people who want to take tea in summer too. This black tea needs to be commercialized and will get market attention as it has great potential to get consumers attraction.